Track technology proceedings of a conference organized by the Institution of Civil Engineers and held at the University of Nottingham, 11-13 July 1984. (Thomas Telford, 1985)
Aimed at civil engineers, these papers focus on the impact of track technology on heavy haul operations, and the design, operation, and maintenance of a mass transit system. The concluding papers discuss subgrade requirements and the application of geotextiles.